Organ complications after CD19 CAR T-cell therapy for large B cell lymphoma: a retrospective study from the EBMT transplant complications and lymphoma working party - Penack, Olaf; Peczynski, Christophe; Koenecke, Christian; Polge, Emmanuelle; Sanderson, Robin; Yakoub-Agha, Ibrahim; Fegueux, Nathalie; Daskalakis, Michael; Collin, Matthew; Dreger, Peter; Kröger, Nicolaus; Schanz, Urs; et al. (Frontiers in immunology, 2023)
We investigated ≥ grade 3 (CTC-AE) organ toxicities for commercial CD19 chimeric antigen receptor T cell (CAR-T cell) products in 492 patients (Axi-Cel; n = 315; Tisa-Cel; n = 177) with Large B-cell Lymphoma in the European Society for Blood and Marrow Transplantation (EBMT) CAR-T registry. The incidence of ≥ grade 3 organ toxicities during the first 100 days after CAR-T was low and the most frequent were: renal (3.0%), cardiac (2.3%), gastro-intestinal (2.3%) and hepatic (1.8%). The majority occurred within three weeks after CAR-T cell therapy. Overall survival was 83.1% [79.8-86.5; 95% CI] at 3 months and 53.5% [49-58.4; 95% CI] at one year after CAR-T. The most frequent cause of death was tumour progression (85.1%). Non-relapse mortality was 3.1% [2.3-4.1; 95% CI] at 3 months and 5.2% [4.1-6.5; 95% CI] at one year after CAR-T. The most frequent causes of non-relapse mortality were cell-therapy-related toxicities including organ toxicities (6.4% of total deaths) and infections (4.4% of total deaths). Our data demonstrates good safety in the European real-world setting.